2013
DOI: 10.1186/cc12510
|View full text |Cite
|
Sign up to set email alerts
|

Additive value of blood neutrophil gelatinase-associated lipocalin to clinical judgement in acute kidney injury diagnosis and mortality prediction in patients hospitalized from the emergency department

Abstract: IntroductionAcute kidney injury (AKI) is a common complication among hospitalized patients. The aim of this study was to evaluate the utility of blood neutrophil gelatinase-associated lipocalin (NGAL) assessment as an aid in the early risk evaluation for AKI development in admitted patients.MethodsThis is a multicenter Italian prospective emergency department (ED) cohort study in which we enrolled 665 patients admitted to hospital from the ED.ResultsBlood NGAL and serum creatinine (sCr) were determined at ED p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 44 publications
4
67
0
1
Order By: Relevance
“…The AUC for NGAL predicting AKI at presentation was 0.80 at admission (T0), which increased to 0.90 when added to the ED physician's initial clinical judgment. This was significantly greater compared to the AUC of the T0 estimated glomerular filtration rate obtained either by modification of diet in renal disease equation (0.78) or Cockroft-Gault formula (0.78) (p = 0.022 and p = 0.020, respectively) [42].…”
Section: Ngal Point-of-care Testingmentioning
confidence: 61%
“…The AUC for NGAL predicting AKI at presentation was 0.80 at admission (T0), which increased to 0.90 when added to the ED physician's initial clinical judgment. This was significantly greater compared to the AUC of the T0 estimated glomerular filtration rate obtained either by modification of diet in renal disease equation (0.78) or Cockroft-Gault formula (0.78) (p = 0.022 and p = 0.020, respectively) [42].…”
Section: Ngal Point-of-care Testingmentioning
confidence: 61%
“…Emergency departments (ED) have a growing role in hospital admissions (6), but only a few studies have addressed AKI in the ED (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a multi-centre study in 665 patients admitted to hospital from the emergency department showed that adding serial pNGAL results to clinical judgement improved the prediction of AKI [ 10 ]. Results of further studies are awaited to decide how best to utilise novel AKI biomarkers in the emergency setting.…”
Section: In the Emergency Departmentmentioning
confidence: 86%